2018
DOI: 10.1002/mma.4718
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis in Peru using a vector‐host model: Backward bifurcation and sensitivity analysis

Abstract: The final goal of control policies in neglected vector‐borne diseases in developing countries is to protect humans. These vector‐borne diseases include leishmaniasis, dengue, chagas, and malaria. The traditional control measures for vector‐borne diseases, as with any other illnesses, suggest to reduce the basic reproduction number R0 below the value 1. This strategy is not necessarily sufficient when a backward bifurcation occurs. Because of its worldwide relevance, we are interested in modeling cutaneous lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Various forms of compartmental models for infectious diseases have been formulated [7]. Several models studying the transmission dynamics of CL have been proposed [8][9][10][11][12][13][14]. See [15,16] for a review of mathematical models for visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%
“…Various forms of compartmental models for infectious diseases have been formulated [7]. Several models studying the transmission dynamics of CL have been proposed [8][9][10][11][12][13][14]. See [15,16] for a review of mathematical models for visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous leishmaniasis is a skin infection caused byLeishmania microparasite that is transmitted by female-sandfly bites. 4,5 This neglected disease is the most common form of leishmaniasis, which results in scarring, psychological disorders, and physical disabilities. 6 Yanik et al 7 found that cutaneous leishmaniasis patients with active lesions have the lowest quality of life than that of the other groups because permanent scar formation, social stigmatization produce anxiety, depressive symptoms, decreased body satisfaction, and low quality of life in patients.…”
Section: Introductionmentioning
confidence: 99%
“…This endemic neglected disease is a worldwide health problem in the Eastern and Western Hemisphere. 4,5,7,8 In the Eastern Hemisphere, cutaneous leishmaniasis is endemic in Asia (Iran, Iraq, Pakistan, India, Afghanistan, Turkmenistan, and Uzbekistan), Africa (Algeria, Sudan, Ethiopia, Kenya, and Egypt), and in Southern Europe (Italy, Portugal, Spain, Ukraine, Bulgaria, Greece, Croatia, and France). In the Western Hemisphere, cutaneous leishmaniasis is endemic in some parts of United States, Mexico, Costa Rica, Nicaragua, Honduras, Brazil, Colombia, Ecuador, Peru, and Venezuela.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations